A STUDY OF THE RELATIONSHIP BETWEEN INTERNAL PSYCHOLOGICAL FACTORS AND ACHIEVEMENT MOTIVATION IN STUDENTS - Nazarli, Rovshan (Health and Society, 2024)
The article is devoted to internal psychological factors and directions of its research. In this article, internal psychological factors are clarified, directions of problem research are investigated, including mechanisms of influence of internal psychological factors on success motivation. the internal psychological factors that determine the success motivation of students are investigated. Here, the influence levels of internal factors on success motivation are studied, including the mechanisms of success psychology and the factors that play a fundamental role in personality success. The research showed that students at medium and high levels tend to succeed and prefer medium risk levels. Those who are afraid of failure either prefer small or, on the contrary, a very high level of risk. It was determined that the higher the student’s motivation to succeed, the stronger the desire to achieve the goal and take risks. At the same time, hope for success is more important than weak motivation to succeed. It has been found that people who are motivated and have high hopes for success tend to avoid high risks.